OHP-032 Involvement of pharmacists from the alpes-maritimes fire and rescue services (sdis06) during the terrorist attack of 14 july 2016 in nice, france. (25th February 2017) - Bertrand, B; Lhommeau, AD; Vittorietti, D; Josse, D; Duchêne, ML
Abstract : Background: On the evening of 14 July 2016, a truck was deliberately driven into a crowd celebrating Bastille Day on the Promenade des Anglais in Nice, France, resulting in 86 deaths and 434 injuries. The SDIS06 rescuers, including physicians (18), nurses (36), pharmacists (3) and psychologists were immediately engaged. A field hospital (FH) was set up next to the incident zone. Purpose: To analyse the added value of the pharmacists during the rescue operation to optimise the quality of patient care. Material and methods: Feedback collected from each responder involved were analysed in order to identify the strengths, weaknesses and possible improvements. Results: 45 min after the first alert, the FH was fully operational at the scene of the terrorist attack. Additional backup teams were on hold ready for action. On the scene, emergency actions were medical triage. Victims categorised as 'extreme emergencies' (20) were directly evacuated to the trauma centre. Those categorised as 'absolute emergencies' (15) and 'relative emergencies' (55) were transported to the FH. Most victims had polytraumas with internal and/or external injuries. 1 pharmacist was at the FH to deliver drugs and medical devices to physicians and nurses. Another pharmacist, at the central pharmacy, prepared additional deliveries of drugs, medical devices needed by the FH and organised the reception of 30 additional oxygen bottles. 1 pharmacist was helping by telephone and 1 more was on standby. Drips, splints and wound dressings were the main requested items to be delivered . The FH contents were adequate. The number of pharmacists involved was high enough to respond to additional needs Conclusion: The involvement of the SDIS 06 pharmaceutical team was found to be effective and helpful in the victims' care management to respond to the breadth of the disaster. Pharmacists are essential for drugs and medical dispensation and for anticipating needs. The pharmacists' team mobilisation system is efficient. A taskforce group analyses pharmaceutical feedback. Three axes of improvement were established: the usefulness of preparing ready to use kits for intubation and infusion, regular training of pharmacists with physicians and nurses to improve the efficiency of drug delivery during mass casualties events and a good knowledge of the use of medical devices. No conflict of interest